Improving the Predictive Value of Prion Inactivation Validation Methods to Minimize the Risks of Iatrogenic Transmission With Medical Instruments - Moudjou, Mohammed; Castille, Johan; Passet, Bruno; Herzog, Laetitia; Reine, Fabienne; Vilotte, Jean-Luc; Rezaei, Human; Béringue, Vincent; Igel-Egalon, Angélique (Frontiers in Bioengineering and Biotechnology, 2020)
Prions are pathogenic infectious agents responsible for fatal, incurable neurodegenerative diseases in animals and humans. Prions are composed exclusively of an aggregated and misfolded form (PrPSc) of the cellular prion protein (PrPC). During the propagation of the disease, PrPSc recruits and misfolds PrPC into further PrPSc. In human, iatrogenic prion transmission has occurred with incompletely sterilized medical material because of the unusual resistance of prions to inactivation. Most commercial prion disinfectants validated against the historical, well-characterized laboratory strain of 263K hamster prions were recently shown to be ineffective against variant Creutzfeldt-Jakob disease human prions. These observations and previous reports support the view that any inactivation method must be validated against the prions for which they are intended to be used. Strain-specific variations in PrPSc physico-chemical properties and conformation are likely to explain the strain-specific efficacy of inactivation methods. Animal bioassays have long been used as gold standards to validate prion inactivation methods, by measuring reduction of prion infectivity. Cell-free assays such as the real-time quaking-induced conversion (RT-QuIC) assay and the protein misfolding cyclic amplification (PMCA) assay have emerged as attractive alternatives. They exploit the seeding capacities of PrPSc to exponentially amplify minute amounts of prions in biospecimens. European and certain national medicine agencies recently implemented their guidelines for prion inactivation of non-disposable medical material; they encourage or request the use of human prions and cell-free assays to improve the predictive value of the validation methods. In this review, we discuss the methodological and technical issues regarding the choice of i) the cell-free assay, ii) the human prion strain type, iii) the prion-containing biological material. We also introduce a new optimized substrate for high-throughput PMCA amplification of human prions bound on steel wires, as translational model for prion-contaminated instruments.